2001
DOI: 10.1007/s11916-001-0071-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of chronic daily headache

Abstract: Despite no clear explanation of the mechanism underlying chronic daily headache, sensitization of central nociceptive neurons is one possibility. Either prolonged activation of peripheral nociceptors or any factors that can alter the endogenous pain control system can trigger this process. A decrease in platelet serotonin has been observed in patients with chronic tension-type headache as well as migraine patients with medication-induced headache. It was also shown that chronic analgesic exposure led to change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Recently, a polymorphism of the gene coding for tryptophan hydroxylase, the rate-limiting enzyme in serotonin biosynthesis, was shown to be associated with anger-related traits of personality [31]. Finally, recent studies suggested that patients with chronic daily headache have a significant impairment of serotonin metabolism [32,33]. So the dysfunction of cerebral serotonergic system seems to be one of the key features in the mechanism of transformation of an episodic to a chronic form of headache and it may play a role in the abnormalities in anger experience and control observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a polymorphism of the gene coding for tryptophan hydroxylase, the rate-limiting enzyme in serotonin biosynthesis, was shown to be associated with anger-related traits of personality [31]. Finally, recent studies suggested that patients with chronic daily headache have a significant impairment of serotonin metabolism [32,33]. So the dysfunction of cerebral serotonergic system seems to be one of the key features in the mechanism of transformation of an episodic to a chronic form of headache and it may play a role in the abnormalities in anger experience and control observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to peripheral tissues or chronic nociceptive input may increase the sensitivity of nociception to produce peripheral sensitization [16,25]. During the migraine state, neuropeptides (substance P, calcitonin gene-related peptide, and neurokinin A) released from nerve fibers react with the blood vessel walls and produce a sterile inflammation [26].…”
Section: Peripheral and Central Sensitizationmentioning
confidence: 99%
“…During the migraine state, neuropeptides (substance P, calcitonin gene-related peptide, and neurokinin A) released from nerve fibers react with the blood vessel walls and produce a sterile inflammation [26]. It may be that repeated episodes of this neurogenic inflammation could chronically sensitize nociceptors, lowering the threshold for future attacks, and also lead to spontaneous activity and expansion of receptive fields of nociceptors [16,25].…”
Section: Peripheral and Central Sensitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tryptophan metabolism pathway has a prominent position in the pathologic process of neurodegenerative diseases, and acts through various regulations. A good example is the serotonin level in headache patients, which was typically abnormal [ 18 , 19 ]. Kynurenic acid has the effect of protection on CNS, while kynurenine and quinolinic acid could be neurotoxic [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%